Near-Peer Mentorship: A Model for Private Music Instruction in an Underserved Community. Issue 1 (July 2020) - MacLeod, Rebecca B.; Blanton, Christen; Lewis, Jessica; Ortiz, Dixie
The case presented in this study focused on the experiences of students enrolled in a Saturday day music program situated in an underserved community. Students in this community represent a wide variety of cultural backgrounds, and we were interested in whether younger students in the program would benefit from receiving lessons from an older student from the same community. This case study was bound by the shared experiences of the participants who engaged in music teaching and learning through this community music program. Data included the following: student surveys, participant interviews, private lesson and orchestra class observations, and teacher assessments. Overall, near-peer mentorship was beneficial. The majority of participants in this study experienced gains in performance skills. Interviews with the mentors revealed several benefits from tutoring a younger student, including self-analysis of instrument performance, positive feelings gained from helping others, and social benefits. The fifth-grade students who were assigned a mentor reported that they learned instrument-specific skills from their mentor and felt more comfortable and confident playing different songs because instruction was individualized.